Técnicas racional emotivo conductual del ABC para optimizar la inteligencia emocional en las estudiantes del tercer año de bachillerato unificado A del colegio de bachillerato Pío Jaramillo Alvarado, de la ciudad de Loja, periodo 2013-2014 - Marin Encalada, Alexandra Paola (2015)
For the present research the objective was: apply the techniques Rational Emotive Behavioral ABC, for optimize the emotional intelligence; was a study descriptive of court a cross and a design quasi-experimental, was applied a survey and the questionnaire of management emotional intelligence of Ruiz in a shows of 15 students of third year of baccalaureate unified. Was used methods as: inductive-deductive, synthetic, analytic, historic and logic; also the method comprehensive, diagnostic, of elaboration and application of models and valuation of the effectiveness of the alternative. Results: in the diagnostic of 86,67% of the students always make decisions important of irrational way. Before of intervention (pre-test) the 93,33% never resolved the conflicts with a communication effective. Then of the intervention (post-test), the 60,00% always keep Self Control. By means of r (x. y) = 0499, the intervention was positive moderate. Conclusions: trend existed of the decision making irrationally, never resolved the conflicts with a communication effective and then of intervention improved the conflict resolution. The intervention was positive moderate.